PENGARUH STAGGER ANGLE TERHADAP PRESSURE RATIO KOMPRESOR AKSIAL MULTISTAGE - Akhsan Yusufi; Setyo Nugroho; Achmad Bahrul Ulum (PROSIDING SNAST, 2018)
Axial compressors are one of the most widely used fluid flow impeller engines in gas turbines and turbo jet engines. The compressor rotates at high speed, adding energy to the airflow while at the same time compressing into a smaller space. To obtain a better pressure ratio, modify the angle on the rotor blade, in order to reduce aeerodynamic losses such as stalls and increase the pressure ratio. The variations used are -5˚ and + 5˚. Both variations will be compared to get the best results to reduce the occurrence of stall and increase pressure ratio. Laying variations on the first rotor. Material type for blade compressor using Aluminum alloy with die casting making technique. In axial compressor testing required several measuring devices, such as anemometer, manometer, temperature sensor, and proximity sensor. This axial compressor will be rotated up to a top speed of 1100 rpm using a Fuel motor. The results obtained as a whole indicate that the variation of stagger angle is very influential on pressure ratio. This occurs in the variation of stagger angle -5˚ at 500,650 rpm, and 950 with a pressure value of 1.00208, 1.00317, and 1.008 pa. This causes the effect of rpm to ΔPlocal bias increases 8% to 16%. From the research results obtained the best angle in reducing aerodynamic losses and increase pressure ratio that is on angle variations -5˚.